The interaction of truthful and deceptive information - Verigin, Brianna L. (Psychology, crime & law, 2020)
Research consistently shows that truthful accounts are richer in detail than deceptive accounts. It is unknown, however, how interviewees strategically regulate the information they provide when their accounts contain both truthful and deceptive information. This study examined how truths and lies interact, and whether interviewees’ self-reported strategies reflect such interactions. Participants (n = 144) provided one statement consisting of two elements. We manipulated the veracity of these elements, with participants allocated to either both truthful, both deceptive, or one truthful and the other deceptive conditions. Results indicated that interviewees calibrate the richness of detail provided in the first element of their statement based on the veracity of the following element. Moreover, our exploratory tests revealed that lies become more detailed when they are flanked by truthful information relative to when they are flanked by other deceptive information. The finding that truthful and deceptive information interacts to influence detail richness provides insight into liars’ strategic manipulation of information when statements contain a mixture of truths and lies. Strategic manipulations of this kind could potentially threaten the reliability of commonly used verbal lie detection tools. This study also offers insight to legal practitioners who rely on baseline deviations to assess credibility.